THE EFFECT OF THE GROWLEARN APPLICATION-ASSISTED PROBLEM-BASED LEARNING MODEL ON THE CRITICAL THINKING SKILLS OF GRADE IV ELEMENTARY SCHOOL STUDENTS: PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN APLIKASI GROWLEARN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD - Salsa Salsa Bela Anggraini; Sekar Dwi Ardianti; Erik Aditia Ismaya (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
The development of critical thinking skills is a fundamental goal of 21st-century elementary education, particularly in Integrated Natural and Social Sciences (IPAS) learning. However, many elementary students still demonstrate low levels of critical thinking due to teacher-centered instructional practices that limit active problem solving. This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by the GrowLearn application on the critical thinking skills of fourth-grade elementary students. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The sample consisted of 64 fourth-grade students divided into an experimental class and a control class. Data were collected through essay-based critical thinking tests administered as pretests and posttests, supported by classroom observations. Data analysis included normality tests, homogeneity tests, independent sample t-tests, and N-Gain analysis. The results showed that the posttest mean score of the experimental class (89.71) was significantly higher than that of the control class (68.61), with a significance value of 0.000 (< 0.05). The N-Gain analysis indicated a high category improvement in the experimental group, while the control group showed moderate improvement. These findings demonstrate that the implementation of PBL assisted by the GrowLearn application has a significant positive effect on students’ critical thinking skills. The novelty of this study lies in the integration of a digital learning application specifically designed to align with the syntax of Problem Based Learning, providing a more structured and contextual learning experience in IPAS instruction at the elementary level.